QJava: A Monadic Java Library for Quantum Programming - Vizzotto, Juliana Kaizer; Calegaro, Bruno Crestani (Revista de Informática Teórica e Aplicada, 2015)
To help the understanding and development of quantum algorithms there is an effort focused on the investigation of new semantic models and programming languages for quantum computing. Researchers in computer science have the challenge of deve loping programming languages to support the creation, analysis, modeling and simulation of high level quantum algorithms. Based on previous works that use monads inside the programming language Haskell to elegantly explain the odd characteristics of quantum computation (like superposition and entanglement), in this work we present a monadic Java library for quantum programming. We use the extension of the programming language Java called BGGA Closure, that allow the manipulation of anonymous functions (closures) inside Java. We exemplify the use of the library with an implementation of the Toffoli quantum circuit.